2015
DOI: 10.17148/iarjset.2015.21208
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Application of Cu-TiO2 Nanaocomposites in Photodegradation of Methyl Red (MR)

Abstract: TiO 2 is used as photo catalyst because of its high oxidation power, stability and non toxicity.Cu-TiO 2 nanocomposites was prepared by a adopting the solution impregnation method. After characterization for crystalline phase and particle size by XRD analysis, SEM analysis was carried out to seen morphology of samples, Surface area of TiO 2 and Cu-TiO 2 were analysed by BET. Both the prepared TiO 2 and synthesized Cu-TiO 2 nanocomposites were used as photo catalyst in the photo-degradation of methyl red. The P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Figure 8 showing the photodegradation of methyl red dyes with Titania and Cu-TiO 2 nanocomposites. The maximum photo-degradation is found in case of Cu modified Titania and whereas in case of Titania less photodegradation occurs [43]. This is because that the surface of Titania different from Cu modified Titania.…”
Section: Size and Structure Of The Photocatalystmentioning
confidence: 90%
See 2 more Smart Citations
“…Figure 8 showing the photodegradation of methyl red dyes with Titania and Cu-TiO 2 nanocomposites. The maximum photo-degradation is found in case of Cu modified Titania and whereas in case of Titania less photodegradation occurs [43]. This is because that the surface of Titania different from Cu modified Titania.…”
Section: Size and Structure Of The Photocatalystmentioning
confidence: 90%
“…The surface of the photocatalyst is positively charged below isoelectric point and carries a negative charge above it. Figures 5-7 showing the effect of pH on the photodegradation of methyl red [43], EBT [38] and Oxalic Acid [44]. The Photodegradation of Methyl Red is found maximum at 5pH because the methyl Red is the cationic dye which adsorb easily on the surface of Titania ( Figure 5).…”
Section: Effect Of Phmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially the degradation of pollutant increases with an increase in catalyst concentration and decomposition found to be directly proportional to catalyst dose. This enhanced efficiency of the process may be due to the fact that increases in catalyst dose resultantly increase in catalyst surface area for the adsorption of pollutants [41,42]. The effect of catalyst dose on BOD, COD, and nitrogen of SHWW shown in Fig.…”
Section: Effect Of Initial Catalyst Concentrationmentioning
confidence: 99%
“…The efficiency of the photocatalytic oxidation process is highly dependent upon the pH of the solution and is considered one of the critical parameters of process because it determines the degree of ionization and sturdily affects the photocatalyst surface charge [44][45][46]. Various researchers have studied the effects of different pH on the efficiency of the photocatalysis oxidation process and reported that maximum degradation by titanium dioxide occurs at low pH because in acidic medium the TiO 2 surface becomes positive and adsorbs the pollutant very easily [41,47,48]. Therefore, to see the effect of pH on BOD, COD, and nitrogen removal efficiency of the photocatalytic oxidation process it was varied between 1-11 (Fig.…”
Section: Effect Of Phmentioning
confidence: 99%